Branding Difablepreneur Sebagai Rekonstruksi Stigma Sosial Penyandang Difabel di Graha Nawasena Dinas Sosial Kota Denpasar - Hudiana, Chandra Utitha; Zuryani, Nazrina; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 5 No 1 (2025): JISSOROT, 2025)
This study aims to analyze the reliable branding of difablepreneurs as an effort to reconstruct social stigma faced by persons with disabilities at Graha Nawasena, under the Denpasar City Social Agency. Social stigma, including negative labeling, stereotypes of incapability, societal exclusion, and discrimination, hinders the independence of persons with disabilities affiliated with Graha Nawasena, encompassing organizations such as Pertuni, Gerkatin, HWDI, NPCI, and Rumah Berdaya. Employing a descriptive qualitative approach and drawing on Erving Goffman’s stigma theory, this study examines identity management strategies through interviews, observations, and documentation with informants, including visually impaired and physically disabled individuals. Findings reveal that stigma in Denpasar stems from societal misconceptions related to karma beliefs and biased media representations. The Denpasar City Social Agency established Graha Nawasena as a hub for difablepreneur empowerment through skill training to enhance professionalism and economic independence. Difablepreneurs manage stigma by passing to conceal disabilities, covering to highlight competencies, and coming out to embrace their identities in public events. The difablepreneur community fosters a new identity, supported by the Social Agency’s social media narratives, weakening negative perceptions of persons with disabilities. The study concludes that the difablepreneur program effectively reconstructs stigma, though it remains an ongoing process requiring more time, with persistent challenges from misconceptions that need addressing. Recommendations include innovating similar programs, raising awareness of the potential of persons with disabilities, expanding partnerships by the Social Agency, and encouraging community support for difablepreneur products to accelerate shifts in social perceptions. Keywords: difable, social stigma, difablepreneur, Graha Nawasena, stigma reconstruction.